Identificación de habilidades Socioemocionales y salud mental en profesores de Educación Superior: Validez de constructo - Jiménez Macías, Iván Ulianov (2023)
In the educational sector, socio-emotional skills (HSE) are skills for managing emotions and behaviors that benefit social relationships and the achievement of educational objectives, having them can favor mental health (MH) and the well-being in higher education teachers who affect the training of future professionals, for this reason it is considered essential have instruments that assess these aspects reliably. The objective was to carry out the construct validity analysis of the Inventory of Socioemotional Skills and Mental Health for Teachers "IHSM-P" of higher education. The sample was made up of 282 professors and the analysis of validity was through exploratory factor analysis. The validity of construct was carried out using the exploratory factorial analysis technique (AFE) and the verification of the pertinence of the data was through the test Kaiser Meyer Olkin (KMO) and Bartlett's sphericity. The results showed correspondence with the theoretical proposal by recognizing six factors, integrating 60% of proposed items. Reliability was optimal (Alpha of Cronbach: 0.907), and relevant for the different factors found (Cronbach's Alpha >0.70). It is concluded that the IHSM-P is an instrument that has adequate psychometric characteristics.